Legal responses to child endangerment on farms: Research methods - Christopher P. Benny; Dorianne Beyer; Madeline Krolczyk; Barbara C. Lee (Frontiers in Public Health, 2022)
In the US agriculture (including ranching) is among the most dangerous industries and it is the only one where children of any age are permitted in the worksite. Whether working or not, children are at risk of serious injury or death when present among the many hazards associated with agricultural work. In most cases the proximate cause of a traumatic incident involving a child (<18 years) is an adult's choice to allow the child's presence in a high-risk situation. Yet, little is known about the legal repercussions for a responsible adult when such events occur. With an overarching goal to enhance the culture of safety for children in agricultural settings, this project includes three phases: (1) identification and collection of public records and news reports regarding legal action following a childhood agricultural injury or fatality; (2) analysis of the proposed or imposed legal responses following these agricultural injuries and fatalities; and (3) development of recommendations for public agencies responding to events that lead to a criminal complaint or the imposition of non-criminal child welfare or other civil measures. This paper describes the project's mixed methods study design that yielded extensive details on 12 legal cases as well as perspectives from key informants on the strengths and limitations of legal responses to child endangerment on farms. Integration and analyses of data from quantitative and qualitative sources will be used to generate recommendations, including guidelines and protocols, for key stakeholder groups.